Determination of moisture content in sunflower meal by reflection NIR spectroscopy - Hutsalo, Inna; Litvynchuk (Vorontsova), Svitlana; Nosenko, Tamara; Nosenko, Volodymyr (My University, 2016)
Thus, it is possible to determine moisture content of sunflower meal using obtained calibration equations and wavelengths mentioned above. The study of reflectance spectra peculiarities makes it possible to more widely use NIR spectroscopy method for rapid determination of fat, protein, moisture and other substances content in oilseeds, in their byproducts and meals (whether it be storage or processing stages).
Keywords: кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; infrared spectroscopy; reflectance spectra; sunflower meal; moisture content; ІК-спектри соняшнику; вміст вологи борошна; відбивна спектроскопія; ИК-спектры подсолнечника; содержание влаги в муке; отражательная спектроскопия; кафедра фізики та професійної безпеки